JUMPA Vol.2 No.1 Feb 2015 STRUKTUR MODAL PERUSAHAAN: DETERMINAN DAN IMPLIKASINYA: STRUKTUR MODAL PERUSAHAAN: DETERMINAN DAN IMPLIKASINYA - Mustanwir Zuhri Fakultas Ekonomi dan Bisnis Perbanas Institute (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2015)
Writing this paper aims to elaborate and explore the determinants and implications of the company's capital structure. Determinants of capital structure including income taxes, profitability, and the size of the company, while the factors that influenced the structure of capital is the return on investment, return on assets, earnings per share, and Tobin's Q. This study is a qualitative as well as literature and is done by comparing the results research or concepts previously been rmapan to obtain confirmation as well as a critique of the research results. The concept used in the discussion is the pecking order theory, capital costs, deductible expenses, economies of scale, as well as leverage and its relation to investment returns, earnings per share, and the stock price. The results of the analysis concluded that from several previous studies found that the relationship between the determinants and effects of capital structure although it varies but can be explained by using the appropriate concept. Advice given on the outcome of this discussion is that in the understanding of social phenomena, including the phenomenon of business, you should use a contingency approach and examined the assumptions underlying concept chosen to criticize the phenomenon of referred business.